Investigations on the Influence of Viscoelasticity on the Swell Behaviour and Flow Instabilities of Carbon Black-Filled Rubber Compounds - Schöppner, Volker; Kleinschmidt, Dennis; Hopmann, C.; Limper, A.; Fey, F.; Facklam, M.; Schön, M.

Investigating Different Methods for Numerical Simulation of Temperature Development in a Feed Section of a Single-Screw Extruder - Schöppner, Volker; Brüning, Florian

Integration of IR Based Inline Measurement Systems of the Surface Temperature of Square Hollow Profiles in an Extrusion Process - Schöppner, Volker; Köllermeier, Jonas

Investigation of the Pressure-Throughput Behavior of Different Spiral Shearing Sections on an Analytical and Simulative Basis - Schöppner, Volker; Frank, Maximilian

Modelling of the material degradation of polypropylene on the co-rotating twin-screw extruder - Schöppner, Volker; Altepeter, Matthias; Wanke, S.

Weiterentwicklung eines Verfahrens zur Korrektur von Wandgleiteffekten im Rahmen rheologischer Messungen an gefüllten Kautschukmischungen - Schöppner, Volker; Kleinschmidt, Dennis; Nillius, U.; Hopmann, C. (GAK)

Rückführung zerkleinerter Organobleche - Moritzer, Elmar; Kröker, M.; Scholle, Maximilian

Teilchen-Kunde - Stäube beim mechanischen Recycling faserverstärkter Thermoplaste - Hopp, Matthias; Tölle, Lisa

Vorteilhaftes Prozessverhalten von Wave-Schnecken - Schall, Christoph Wilhelm Theodor

Characterization of additively manufactured plastic components for direct screwing - Moritzer, Elmar; Held, Christian

Plasmaaktivierung fehlgeschlagen! - Moritzer, Elmar; Rauen, Dennis (Kunststoffe)

Verbessertes Füllverhalten im Spritzgießprozess durch Schäumen von WPC: Bewertung des Fließverhaltens treibmittelbeladener Polymerschmelzen - Fuhrmann, Anika; Schoch, Rebecca; Rusam, Alexander; Bosse, Michael; Flachmann, Felix; Moritzer, Elmar; Hochrein, Thomas; Bastian, Martin

Influence of Screw Design on Fiber Breakage of Glass Fiber Reinforced Polypropylene in the Injection Molding Process - Moritzer, Elmar; Bürenhaus, Franziska Isabelle (37th International Conference of the Polymer Processing Society (PPS))

Characterization of Fiber Dust Resulting from Recycling of Carbon Fiber-Reinforced Thermoplastics (CFRP) and Their Cell Toxicity - Hopp, Matthias; Tölle, Lisa; Monsé, C.; Rosenkranz, N.; Haibel, N.; Walter, D.; Bünger, J.; Westphal, G. (Journal of Material Science and Chemical Engineering)

Multimaterial Injection Moulding of Thermosets and Elastomers - Moritzer, Elmar; Scheiermann, Denis; Bellusova, Denisa; Klie, Benjamin; Giese, Ulrich (ScienceBG)

Spritzgießen hochtemperaturbeständiger Baugruppen aus Duromeren und Elastomeren - Moritzer, Elmar; Scheiermann, Denis; Bellusova, Denisa; Klie, Benjamin; Giese, Ulrich (Kunststoffland NRW)

Messtechnische Ermittlung der Strukurintensität bei spritzgegossenen, faserverstärkten Kunststoffen - Moritzer, Elmar; Netzband, Dennis; Ujma, Andreas

Investigation and Improvement of Processing Parameters of a Copper-Filled Polymer Filament in Fused Filament Fabrication as a Basis for the Fabrication of Low-Porosity Metal Parts - Moritzer, Elmar; Elsner, Christian Lennart (Macromolecular Symposia)

Development of a Procedure for the Assessment of Material Potentials under Consideration of the Weld Seam Quality for Multi-Material Applications in the FDM Process - Moritzer, Elmar; Wächter, Julian (Macromolecular Symposia)

Reactive Direct Bonding of Digital Light Process Components - Moritzer, Elmar; Driediger, Christine (Macromolecular Symposia)
Keywords: digital light processing; material combination; reactive direct bonding; vat photopolymerization

Mit Gestaltungsrichtlinien zum Erfolg - Moritzer, Elmar; Elsner, Christian Lennart (Kunststoffe)

Separation Of Multi-Component Parts For Mechanical Recycling – Study About Basic Approaches Using A Heating Process - Hopp, Matthias; Schäffer, Leon

Dimensionierung und Optimierung von im FDM-Verfahren 3D-gedruckten Direktverschraubungen aus ABS - Moritzer, Elmar; Held, Christian; Hillemeyer, Johannes (Joining Plastic)

Mit der richtigen Auslegung zur sicheren Verbindung - Moritzer, Elmar; Held, Christian; Hopmann, C.; Kramer, M. (Kunststoffe)

Die Vielseitigkeit von Beschichtungen im Spritzgießwerkzeug- und Formenbau - Moritzer, Elmar; Rauen, Dennis; Schilp, Catharina; Scholle, Maximilian (Zeitschrift Kunststofftechnik)

Reactive Direct Bonding of Digital Light Process Components - Moritzer, Elmar; Driediger, Christine (Macromolecular Symposia)

Development of Simulation Based Assistant Systems for Automatic Process Monitoring and Derivation of Recommendations to Optimize a Profile Extrusion Line - Schöppner, Volker; Köllermeier, Jonas; Hiesgen, G.; Trippe, J.

Application of a Dynamic Approach to Determine the Optimal Barrel Temperature of Single Screw Extruders - Schöppner, Volker; Köllermeier, Jonas

Development of an Inline-Measurement System of the Surface Temperature of Square Hollow Profiles - Schöppner, Volker; Köllermeier, Jonas

Wave-Schnecken in der Einschneckenextrusion - Dörner, Marius

Untersuchungen zur werkstofflichen Aufbereitung von Post-Consumer-Kunststoffabfällen und Entwicklung eines neuen Aufbereitungsverfahrens - Helmlinger, Lars René

Ein Beitrag zur InMould-Plasma Technologie zur Oberflächenvorbehandlung im Mehrkomponentenspritzgießwerkzeug - Mühlhoff, Frederik Marvin

Ein Beitrag zum Warmgasstumpfschweißen von Kunststoffen - Bialaschik, Max Oliver

Modellierung der Carbonfaserlängenverkürzung - Malatyali, Hatice

Analysis of the Segregation Phenomena of Wood Fiber Reinforced Plastics - Moritzer, Elmar; Flachmann, Felix; Richters, Maximilian; Neugebauer, Marcel (Journal of Composites Science)
Wood–plastic composites (WPC) are enjoying a steady increase in popularity. In addition to the extrusion of decking boards, the material is also used increasingly in injection molding. Depending on the formulation, geometry and process parameters, WPC tends to exhibit irregular filling behavior, similar to the processing of thermosets. In this work, the influence of matrix material and wood fiber content on the flow, mold filling and segregation behavior of WPC is analyzed. For this purpose, investigations were carried out on a flow spiral and a sheet cavity. WPC based on thermoplastic polyurethane (TPU) achieves significantly higher flow path lengths at a wood mass content of 30% than polypropylene (PP)-based WPC. The opposite behavior occurs at higher wood contents due to the different shear thinning behavior. Slightly decreased wood contents could be observed at the beginning of the flow path and greatly increased wood contents at the end of the flow path, compared to the starting material. When using the plate cavity, flow anomalies in the form of free jets occur as a function of the wood content, with TPU exhibiting the more critical behavior. The flow front is frayed, but in contrast to the flow spiral, no significant wood accumulation could be detected due to the shorter flow path lengths.
Keywords: Engineering (miscellaneous); Ceramics and Composites

Numerical Simulation of Solids Conveying in Grooved Feed Sections of Single Screw Extruders - Brüning, Florian; Schöppner, Volker (Polymers 14)
Keywords: Computing Resources Provided by the Paderborn Center for Parallel Computing

A comparison of heuristic, statistical, and machine learning methods for heated tool butt welding of two different materials - Schöppner, Volker; Gevers, Karina; Tornede, A.; Wever, M.; Hüllermeier, E. (Welding in the World)

Material-specific prediction of the optimal joinig parameters for the screw blind rivet joining process - Moritzer, Elmar; Held, Christian; Hillemeyer, J. (Welding in the World)

EFFECT OF SHREDDING PARAMETERS ON THE FORMATION OF AIRBORNE FIBER DUST DURING MECHANICAL RECYCLING OF FIBER-REINFORCED THERMOPLASTICS - Hopp, Matthias; Tölle, Lisa (Proceedings of the 20th European Conference on Composite Materials)

Qualification of Different Carbon Fiber Reinforced Polyether Ether Ketone Materials for the FFF Process - Moritzer, Elmar; Wächter, Julian

Bewertung von IR-Schweißverbindungen an kurzfaserverstärkten Thermoplasten mittels digitaler Bildkorrelation - Gevers, Karina; Schraa, L; Uhlig, K; Töws, P; Stommel, M

Schweißnahtkennwerte für die lebensdaueroptimierte Bauteilauslegung von hochtemperaturbeständigen Thermoplasten - Schöppner, Volker; Vogtschmidt, Sascha

On the Wave to Successful Mixing - Schöppner, Volker; Dörner, M.; Frank, Maximilian; Schall, Christoph

Influence of Processing Glass-Fiber Filled Plastics on Different Twin-Screw Extruders and Varying Screw Designs on Fiber Length and Particle Distribution - Rüppel, Annette; Wolff, Susanne; Oldemeier, Jan Philipp; Schöppner, Volker; Heim, Hans-Peter (Polymers)
Due to their valuable properties (low weight, and good thermal and mechanical properties), glass fiber reinforced thermoplastics are becoming increasingly important. Fiber-reinforced thermoplastics are mainly manufactured by injection molding and extrusion, whereby the extrusion compounding process is primarily used to produce fiber-filled granulates. Reproducible production of high-quality components requires a granulate in which the fiber length is even and high. However, the extrusion process leads to the fact that fiber breakages can occur during processing. To enable a significant quality enhancement, experimentally validated modeling is required. In this study, short glass fiber reinforced thermoplastics (polypropylene) were produced on two different twin-screw extruders. Therefore, the machine-specific process behavior is of major interest regarding its influence. First, the fiber length change after processing was determined by experimental investigations and then simulated with the SIGMA simulation software. By comparing the simulation and experimental tests, important insights could be gained and the effects on fiber lengths could be determined in advance. The resulting fiber lengths and distributions were different, not only for different screw configurations (SC), but also for the same screw configurations on different twin-screw extruders. This may have been due to manufacturer-specific tolerances.
Keywords: Polymers and Plastics; General Chemistry

VALIDATION AND COMPARISON OF FEM-SIMULATION RESULTS OF THE FUSED DEPOSITION MODELING PROCESS UNDER CONSIDERATION OF DIFFERENT MESH RESOLUTIONS - Moritzer, Elmar; Hecker, Felix (Proceedings of the 33rd Annual Freeform Fabrication Symposium)

Analysis of the Segregation Phenomena of Wood Fiber Reinforced Plastics - Moritzer, Elmar; Flachmann, Felix; Richters, Maximilian; Neugebauer, Marcel (Journal of Composites Science)

INVESTIGATION OF THE PROCESS PARAMETERS AND GEOMETRY DEPENDENT SHRINKAGE BEHAVIOR OF RASTER LINES IN THE FUSED DEPOSITION MODELING PROCESS - Moritzer, Elmar; Hecker, Felix (Proceedings of the 33rd Annual Freeform Fabrication Symposium)

Erarbeitung eines methodischen Vorgehens zur merkmalspezifischen Charakterisierung der Verarbeitungseignung von nicht verstärkten und faserverstärkten Kunststoffen im Fused Deposition Modeling am Beispiel von Polyamid 6 - Schumacher, Christian
Das Fused Deposition Modeling (FDM) ist ein Verfahren zur additiven Fertigung (AF), welches von der Firma Stratasys Ltd. (früher Stratasys Inc.) kommerzialisiert wurde. Heute existieren auch FDM Maschinen anderer Hersteller. Im Gegensatz zu den Maschinen von Stratasys können bei diesen die Prozessparameter frei gewählt werden. Dadurch ist die Verarbeitung herstellerfremder Materialien möglich. Wie in allen AF-Verfahren, werden im FDM bestimmte Anforderungen an die zu verarbeitenden Materialien gestellt. Die Materialien sollten daher speziell für das FDM ausgewählt bzw. entwickelt werden. Die für eine gute Verarbeitbarkeit notwendigen Materialeigenschaften sind aktuell jedoch nicht hinreichend bekannt. Vielmehr sind auch keine Vorgehensweisen bekannt, um die Verarbeitungseignung verschiedener Materialien im FDM zu bewerten. Im Rahmen dieser Arbeit werden daher Vorgehensweisen vorgestellt, um die Verarbeitungseignung thermoplastischer Kunststoffe im FDM anhand bestimmter Merkmale zu bewerten. Die Schweißnahtqualität, der Bauteilverzug und die Gestaltungsfreiheit werden als wichtige Merkmale identifiziert. Unter Beachtung relevanter Einflussgrößen werden je Merkmal Probekörper und Prüfmethoden entwickelt, um merkmalspezifische Kennwerte zu definieren. Dadurch ist der Vergleich unterschiedlicher Materialien, unabhängig von der verwendeten Maschine und der Datenaufbereitung, möglich. Letztendlich werden verschiedene Materialmodifikationen auf Basis von PA 6 erstellt und mit Hilfe der vorgestellten Vorgehensweisen untersucht und bewertet.

Simplified Numerical Calculation of the Isothermal, Three-Dimensional, Non-Newtonian Flow Characteristics of Single-Screw Melt-Extruders - Stüker, Daniel; Schöppner, Volker

Non-Isothermal Calculation of the Pressure-Throughput-Characteristics of Single Screw Melt-Extruders - Stüker, Daniel; Schöppner, Volker